Supervisor abuse effects on subordinate turnover intentions and subsequent interpersonal aggression: the role of power-distance orientation and perceived human resource support climate - Richard, Orlando C. (Journal of business ethics, 2020)
Despite mounting evidence that abusive supervision triggers interpersonal aggression, much remains unknown regarding the underlying causal mechanisms within this relationship. We explore the role of turnover intentions as a mediator in the relationship between abusive supervision and subsequent supervisor-rated interpersonal aggression. We use a sample of 324 supervisor–subordinate dyads from nine organizations and find support for this mediation effect. Furthermore, we find that (low) power-distance orientation and (high) perceived human resource (HR) support climate, as important boundary conditions, independently interact with abusive supervision to weaken this positive impact on turnover intentions, thereby reducing interpersonal aggression. We also find via turnover intentions that abusive supervision intensifies interpersonal aggression among high power-distance-oriented individuals when the HR support climate is perceived to be low. Theoretical and practical implications are discussed.